Determinação das bases moleculares da deficiência hereditária de fator VII da coagulação - Flavia Yankous Rabelo (2011)
Introduction: The inherited deficiency of coagulation factor VII (FVII) is the most frequent among rare coagulopathies, with an estimated prevalence of 1: 500,000 inhabitants. It is transmitted as an autosomal recessive inheritance, due to mutations in the gene coding FVII (F7). It presents variable clinical manifestations, from asymptomatic forms to severe bleedings. Molecular studies are rare in non-Caucasian populations. Thus, we studied, at molecular level, a cohort of patients with FVII deficiency, registered at Hemocentro de Belo Horizonte (HBH), Belo Horizonte, Brazil. Methods: All patients diagnosed with FVII deficiency were invited to participate in the study through an invitation letter. We collected clinical data and blood samples between November 2003 and February 2004. Thirty-one (82%) out of 38 patients accepted the invitation; 26 of them (84%) had FVII activity (FVII:C) lower than 50% and 4 patients (13%) had FVII:C slightly over than 50% (included as they presented a hemorrhagic manifestation). FVII:C was not assessed in 1 patient (3%). Patients were clinically evaluated and submitted to laboratory tests, among these, prothrombin time and FVII:C, with different thromboplastins. All exons and intron/exon borders of F7 were amplified and sequenced. Results: Thirteen gene variants were identified. Six (46%) are known genetic variants (Arg304Gln; Thr324Met, c.-323_-313insCCTATATCCT; Glu95Glu; His175His and Arg353Gln) and seven (54%) are new ones (Arg43Lys, Phe84Phe; Gln116Gln; Arg139Arg, Glu142Glu, c.745_747delGTG and Gln281Gln). Conclusion: Most patients with moderate to mild FVII deficiency have polymorphisms or genetic alterations in homozygosis. No association was seen between phenotype and genotype of the patients studied, which corroborates data from the literature.